Health Disparities and Ethnic Classification in Hungary - Inez Zsófia Koller (Journal on Ethnopolitics and Minority Issues in Europe, 2022)
Census and register questionnaires are prepared to obtain general information on society, and their disaggregated findings guide policy makers, economic planners, and researchers. However, their general focus does not necessarily provide information on ethnicity related to health status. Why would this interrelated data be important? The identification of disaggregated ethnic data can be utilised in understanding and eliminating ethnic health disparities. Ethnicity-related demographic data provides extra information about public health for at least two purposes. The first identifies the health needs and special health markers of diverse ethnic groups; the second points out ethnic-related inequalities in healthcare (Villarroel et al., 2018). On the other hand, this method of data collection may easily lead to discrimination and the misuse of data. The aim of this paper is to provide a detailed explanation of why Hungary has chosen to prioritise neutral approaches to ethnic classification over public health interests. It will explain why the Hungarian concept of ethnicity is based on personal affiliation, and provides an insight into the ethnic composition of the country. This includes information on which social, historical, and political constraints have shaped the method of ethnic classification, how granularity is incorporated into the ethnic classification system, and how the data gathered on ethnicity relates to the actual number of people who belong to ethnic minority groups. This is especially in the case of one particular ethnic group, the Roma, for whom ethnicity-based data collection could serve as a proactive tool for easing health disparities in the country, as testified by previous studies carried out over the past fifty years.